Neighbourhoods and City Quarters in Antiquity Design and Experience - Haug, Annette; Hielscher, Adrian; Krüger, Anna-Lena (Decorative Principles in Late Republican and Early Imperial Italy (Decor), 2023)
This volume focuses on the socio-spatial organisation of ancient cities, and more specifically on Late Republican and Imperial Italy. Referring to a praxeological and phenomenological perspective, it looks at neighbourhoods and city quarters as basic categories of design and experience.